Injury of the brachial artery accompanying simple closed elbow dislocation: a case report - Goretti, Claudio; Pari, Carlotta; Puzzo, Agnese; Rizqallah, Yousef; Bonanno, Maria Giovanna; Belluati, Alberto (Acta Biomedica Atenei Parmensis, 2020)
Background: Elbow dislocation is the second common dislocation in adults, after the shoulder. The anatomical proximity to the joint of the brachial artery could lead to concomitant vascular injuries, even if their occurrence remains very rare. Method: It is reported the case of a right-hand-dominant 42-year-old man who sustained a simple closed posterior elbow dislocation of his left elbow, associated to a complete brachial artery rupture. He urgently underwent the reduction of the joint dislocation and an artery-repairing surgical procedure using a graft from ipsilateral saphenous vein. Results: The full functional capacity of the elbow was obtained. Conclusions: The abundance of the brachial artery collateral network may hide the presence of a vascular injury, potentially associated to a closed elbow dislocation. Therefore, a high index of suspicious should be maintained. The Emergency Team plays a crucial role in its early diagnosis, which is essential to avoid irreversible ischemia related damages. A prompt reduction of the joint dislocation and the vascular injury surgical repair are required. Regarding the treatment of the concomitant collateral ligaments and capsular injuries, the indication to proceed to the simultaneous ligaments reconstruction is still controversial in literature.